Annual indirect cost savings in patients with episodic or chronic migraine: post-hoc analyses from multiple galcanezumab clinical trials. (31st December 2022) - Tobin, Joshua; Ford, Janet H.; Tockhorn-Heidenreich, Antje; Nichols, Russell M.; Ye, Wenyu; Bhandari, Rohit; Mi, Xiaojuan; Sharma, Karan; Lipton, Richard B.
Abstract: Aim: This post-hoc analysis estimated annual indirect cost savings with galcanezumab (GMB) treatment in patients with episodic migraine (EM) or chronic migraine (CM). Methods: Data from 4 randomized, Phase 3, double-blind (DB), placebo (PBO)-controlled studies of GMB were analyzed: EVOLVE-1 and EVOLVE-2 (EM, 6-months DB), REGAIN (CM, 3-months DB), and CONQUER (previous failure of 2–4 migraine preventive medication categories, 3-months DB). Indirect costs were calculated at baseline and Month 3 using the first 2 items in Migraine Disability Assessment (MIDAS): (A + B)/60*country specific annual wage (A = days of missed work/school; B = days of reduced productivity at work/school; assuming 60 working days in 3 months). All costs were annualized and expressed in international dollars (Int$) in 2018. ANCOVA models estimated the indirect cost savings as a change from baseline. Secondary analyses determined cost savings by employment and responder status. Results: Patients (>80% females) from EVOLVE-1 and −2 ( n  = 1, 201; mean age 41.9 years), REGAIN ( n  = 759; mean age 41.3 years), and CONQUER ( n  = 453; mean age ∼46.0 years) were analyzed. GMB showed significant indirect cost savings for EM (Int$6256, p  < .0001) and CM (Int$7129, p  = .0002), with substantial savings for patients with previous failure of 2–4 migraine preventive medication categories (EM: Int$5664, p  = .0030; CM: Int$5181, p  = .1300). Compared with PBO, GMB showed significantly greater indirect cost savings for EM ( p  = .0156) and patients with previous failure of 2–4 migraine preventive medication categories ( p  = .0340). Employed patients with CM ( p  = .0018) and with previous failure of 2–4 migraine preventive medication categories ( p  < .0001) had significant cost savings after GMB treatment. GMB showed significant indirect cost savings in patients with a reduction in migraine headache days. Conclusion: GMB treatment resulted in annual indirect cost savings in patients with EM, CM, and with previous failure of 2–4 migraine preventive medication categories, with similar observations in the sensitivity analyses.